TOKSOPLASMOSIS DALAM KEHAMILAN - Suparman, Erna (Jurnal Biomedik : JBM, 2012)
Abstract: Toxoplasmosis in pregnancy causes the Toxoplasma gondii infection in the fetus via the uteroplacental route. There is a very significant positive correlation between the isolation of Toxoplasma from placental tissues and neonatal infection. Laboratory tests commonly performed are anti-Toxoplasma IgG and IgM, and anti-Toxoplasma IgG avidity. Examination should be done in women who are suspected of being infected of Toxoplasma gondii before or during pregnancy, as well as in newborns of mothers infected with Toxoplasma gondii. Food and Drug Administration (FDA) recommends interpreting the results of an anti-Toxoplasma IgM serology test carefully. Doctors can not confirm the diagnosis based solely on one type of toxoplasmosis test. The use of spiramycin during pregnancy causes a decrease in the frequency of vertical transmission. Spiramycin is given to women who are suspected of having acute Toxoplasma infection in the first trimester or in the early second trimester until labor. Spiramycin should not be used as a monotherapy in suspected cases of fetal infection. In pregnant women who have a high likelihood of infection of Toxoplasma gondii or in cases of fetal infection, treatment with spiramycin should include pyrimethamine, sulfadiazine, and folic acid after 18 weeks of gestation.Key words: Toxoplasmosis, pregnancy, fetal infection.Â Abstrak: Toksoplasmosis dalam kehamilan menyebabkan transmisi Toxoplama gondii melalui sirkulasi uteroplasenta ke janin. Terdapat korelasi positif yang sangat bermakna antara isolasi toksoplasma dari jaringan plasenta dan infeksi neonatus. Pemeriksaan laboratorium yang lazim dilakukan ialah anti toksoplasma IgG dan IgM, serta aviditas anti-Toksoplasma IgG. Pemeriksaan tersebut perlu dilakukan pada ibu yang diduga terinfeksi Toxoplasma gondii sebelum atau selama masa kehamilan, serta pada bayi baru lahir dari ibu yang terinfeksi Toxoplasma gondii. Food and Drug Administration (FDA) merekomendasikan untuk menginterpretasikan hasil tes serologi IgM anti toksoplasma dengan cermat. Para dokter tidak boleh menegakkan diagnosis toksoplasmosis hanya berdasarkan satu jenis pemeriksaan. Penggunaan spiramisin selama kehamilan menyebabkan penurunan frekuensi transmisi vertikal. Spiramisin diberikan pada wanita yang diduga mengalami infeksi toksoplasma akut pada trimester pertama atau awal trimester kedua, dan akan diberikan hingga persalinan. Sebaiknya spiramisin tidak digunakan sebagai menoterapi pada kasus yang diduga terjadi infeksi pada janin. Untuk ibu hamil yang memiliki kemungkinan infeksi yang tinggi atau telah terjadi infeksi janin, pengobatan dengan spiramisin harus dibantu setelah usia kehamilan 18 minggu dengan pirimetamin, sulfadiazin, dan asam folat. Kata kunci: Toksoplasmosis, kehamilan, infeksi fetal.